Mediating factors associated with alcohol intake and periodontal condition - Kusu, Yuto; Furuta, Michiko; Kageyama, Shinya; Yamashita, Yoshihisa; Takeshita, Toru (Frontiers in Oral Health, 2025)
BackgroundAlcohol consumption has been reported to increase the risk of periodontal disease and various health abnormalities such as obesity, hyperglycemia, and liver abnormalities. While the link between these health abnormalities and periodontal disease has been established, their potential mediating role in the association between alcohol consumption and periodontal disease remains unclear. Therefore, this study aims to investigate the multiple mediating roles of obesity, hyperglycemia, and liver abnormalities in this association.MethodsA cross-sectional study was conducted on 6,529 individuals aged 35–64 years who underwent workplace health check-ups in 2003 (mean age: 45.7 ± 8.7 years). The periodontal condition was evaluated using the mean pocket depth (PD), and participants were classified into no, light/moderate (alcohol consumption 0.1–29.9 g/day), and heavy (≥30 g/day) drinking groups. Causal mediation analysis was performed.ResultsHeavy drinking had a direct effect on the mean PD. Light/moderate drinking had a indirect effect on the mean PD through the body mass index (BMI), glucose level, alanine aminotransferase level (ALT), with proportion mediated of 25.1%, 8.9%, and 18.9%, respectively. The mediating role of glucose level was found in the association between heavy drinking and the mean PD with proportion mediated of 32.7%.ConclusionThis study confirmed that alcohol consumption was associated with worse periodontal condition among Japanese adults who received workplace health check-ups. This association was partially contributed by several factors such as BMI, glucose level, and ALT.